2015
DOI: 10.1021/acs.organomet.5b00327
|View full text |Cite
|
Sign up to set email alerts
|

Dimers of Nineteen-Electron Sandwich Compounds: An Electrochemical Study of the Kinetics of Their Formation

Abstract: Rate constants for the dimerization of FeCp*C 6 H 6 , RuCp*mes, RhCp 2 , RhCp*Cp, and IrCp*Cp (Cp* = pentamethylcyclopentadienyl; mes = 1,3,5-trimethylbenzene; Cp = cyclopentadienyl) have been investigated by cyclic voltammetry. Rates increased in the order FeCp*C 6 H 6 ≪ RhCp*Cp ∼ RhCp 2 < RuCp*mes and IrCp*Cp. The difference in rates between the Rh compounds and the Ru and Ir species is consistent with the thermodynamic driving forces for dimerization estimated from DFT calculations. However, the sluggish di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In both cases, the reaction is accelerated by visible light (presumably by electron transfer from D 2 to photoexcited A), thus approaching our original concept of activating doping by an external stimulus. , Weakly bonded (Rc-DMBI) 2 behaves similarly to (RhCp*Cp) 2 , while (Fc-DMBI) 2 reacts through a “cleavage first” pathway (apparently with the first and second steps rate-determining at ambient and higher temperatures, respectively) . Cleavage also plays roles for exo,endo -[RuCp*­(1,4-(Me 2 N)­C 6 H 4 )] 2 and (N-DMBI) 2 . , Despite DFT indicating a weak bond, [FeCp*­(C 6 H 6 )] 2 reacts with TIPS-pentacene via the ET-first mechanism; this and the slow dimerization of FeCp*­(C 6 H 6 ) were attributed to a particularly high-energy transition state for this D 2 /D interconversion, perhaps resulting from the greater localization of spin density on the metal, and its reduced extension onto the ligand, for FeCp*­(C 6 H 6 ) than for the 4d and 5d monomers . Finally, (RhCp*Cp″) 2 and exo,exo -[RuCp*­(1,4-(Me 2 N)­C 6 H 4 )] 2 react much more rapidly than any of the other dimers, , consistent with their especially cathodic E (D 2 + /D 2 ) values.…”
Section: Solution Reactivitymentioning
confidence: 95%
See 2 more Smart Citations
“…In both cases, the reaction is accelerated by visible light (presumably by electron transfer from D 2 to photoexcited A), thus approaching our original concept of activating doping by an external stimulus. , Weakly bonded (Rc-DMBI) 2 behaves similarly to (RhCp*Cp) 2 , while (Fc-DMBI) 2 reacts through a “cleavage first” pathway (apparently with the first and second steps rate-determining at ambient and higher temperatures, respectively) . Cleavage also plays roles for exo,endo -[RuCp*­(1,4-(Me 2 N)­C 6 H 4 )] 2 and (N-DMBI) 2 . , Despite DFT indicating a weak bond, [FeCp*­(C 6 H 6 )] 2 reacts with TIPS-pentacene via the ET-first mechanism; this and the slow dimerization of FeCp*­(C 6 H 6 ) were attributed to a particularly high-energy transition state for this D 2 /D interconversion, perhaps resulting from the greater localization of spin density on the metal, and its reduced extension onto the ligand, for FeCp*­(C 6 H 6 ) than for the 4d and 5d monomers . Finally, (RhCp*Cp″) 2 and exo,exo -[RuCp*­(1,4-(Me 2 N)­C 6 H 4 )] 2 react much more rapidly than any of the other dimers, , consistent with their especially cathodic E (D 2 + /D 2 ) values.…”
Section: Solution Reactivitymentioning
confidence: 95%
“…where ΔG diss ⧧ and ΔG dim ⧧ are the barriers for the dissociation of D 2 , inferred from reaction kinetics with an OSC, specifically from the temperature dependence of k′ of eq 7 (see Solution Reactivity section), and the dimerization of D, obtained from variable-temperature variable-scan-rate electrochemical measurements of the reduction/oxidation current ratio for D + /D, respectively. 53 However, in general, we have relied upon DFT calculations of the energies of D 2 and D. In contrast to what is seen for some weakly bound alkyl-and aryl-substituted ethanes, 54 DFT dissociation energetics are not correlated with either crystallographic or DFT central C−C bond lengths (Figure 5). 2,3 However, it is important to remember that bond length depends on orbital overlap and steric effects in D 2 , whereas dissociation energy depends on both D 2 and D stability.…”
Section: ■ Dopant Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentamethylrhodocene dimer (RhCp*Cp) 2 ( N1 ), which is used here as an n-dopant for WSe 2 , is moderately air-stable in the solid state and has been applied to the surface n-doping of the 2D material graphene, carbon nanotubes, and various metal and metal−oxide electrode materials, as well as to the bulk doping of organic semiconductors; moreover, (RhCp*Cp) 2 reacts analogously to the dimeric benzimidazoline-based dimer that we have previously used as an n-dopant for few-layer MoS 2 , with bond cleavage accompanying electron transfer, leading to the formation of two monomeric cations (here (RhCp*Cp) + ), and has a similar effective redox potential ( E ((Rh­Cp*­Cp) + /0.5­(Rh­Cp*­Cp) 2 ) estimated to be ca. −2.0 V vs (FeCp 2 ) +/0 ). , The redox potentials of dopants used in this study are shown in Figure a. Physical characterization using ultraviolet and X-ray photoelectron spectroscopy (UPS and XPS) as well as Raman spectroscopy are used to confirm the doping effects and to understand the underlying doping mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…−2.0 V vs (FeCp 2 ) +/0 ). 25,26 The redox potentials of dopants used in this study are shown in Figure 1a. Physical characterization using ultraviolet and X-ray photoelectron spectroscopy (UPS and XPS) as well as Raman spectroscopy are used to confirm the doping effects and to understand the underlying doping mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%